The Arrangement Unus Testis Nullus Testis in Sexual Violence Crime Cases: Crucial or Over-Regulation? - Mardhiah, Ainal; Susilo, Erwin; Negara, Dharma Setiawan (Jurnal Daulat Hukum, 2025)
The principle unus testis nullus testis is a fundamental evidentiary rule in Indonesian criminal procedure, requiring at least two valid pieces of evidence to convict a defendant. This principle aligns with the negative legal system approach, emphasizing judicial certainty in criminal trials. However, its strict application in cases of sexual violence presents challenges, as these crimes often occur in closed settings where the victim is the sole witness. Recognizing this, Law No. 12 of 2022 on Sexual Violence Crimes introduces a provision that allows a victim's testimony, supported by at least one other piece of evidence, to be sufficient for conviction. This study examines the normative conflict between Article 25(1) of Law No. 12 of 2022 and Article 185(2) KUHAP, which traditionally enforces the unus testis nullus testis principle. By employing a normative juridical approach, this research analyzes the necessity and implications of this special provision, comparing its application with Dutch legal practice, where courts allow supporting evidence beyond direct witness testimony (steunbewijs). The findings suggest that while special considerations for sexual violence cases are justified, Article 25(1) of Law No. 12 of 2022 may constitute over-regulation, as its substance is already accommodated within the existing evidentiary framework of the KUHAP. This research highlights the need for harmonization between special provisions on sexual violence cases and general evidentiary rules to ensure legal certainty while upholding justice for victims. Future legislative reforms should focus on integrating these provisions systematically to prevent redundancy and inconsistencies within Indonesia’s criminal justice system.